2022
DOI: 10.3233/jnd-220810
|View full text |Cite
|
Sign up to set email alerts
|

Slowly Progressive Limb-Girdle Weakness and HyperCKemia – Limb Girdle Muscular Dystrophy or Anti-3-Hydroxy-3-Methylglutaryl-CoA-Reductase-Myopathy?

Abstract: Background: Anti-3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR)-myopathy is a usually rapidly progressive form of immune-mediated necrotizing myopathy (IMNM). Rarer clinical courses show slow progression and resemble the phenotype of limb-girdle dystrophy (LGMD). Objective: We demonstrate the difficulties in differentiating LGMD versus anti-HMGCR-myopathy. Methods: We report on a 48-year-old patient with slowly progressive tetraparesis and hyperCKemia for more than 20 years. Results: Due to myopathic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…A recent retrospective study in patients with IMNM showed that muscle MRI can be useful for monitoring disease activity and that the percentage of STIR+ muscles correlated with higher risk of fat replacement at follow-up, but a specific pattern of involvement was not identified either. 49 Regarding young statin-naïve patients, only few imaging data from case reports are available with similar findings, 11,17 and there are not larger series to allow a proper comparation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent retrospective study in patients with IMNM showed that muscle MRI can be useful for monitoring disease activity and that the percentage of STIR+ muscles correlated with higher risk of fat replacement at follow-up, but a specific pattern of involvement was not identified either. 49 Regarding young statin-naïve patients, only few imaging data from case reports are available with similar findings, 11,17 and there are not larger series to allow a proper comparation.…”
Section: Discussionmentioning
confidence: 99%
“…13,16,19,20 Two recent case reports have attested to muscle imaging evidence of progression from muscle edema to fatty infiltration over the years, demonstrating irreversible muscle damage. 11,17 This fact would suggest that treatment must be prompt, given that immunomodulatory therapy initiated years after onset is usually unsuccessful in controlling the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In others, anti-HMGCR autoantibodies develop without an apparent trigger. The muscle disease can manifest as a rapidly progressive form of IMNM, but in rarer cases shows slow progression and can be erroneously diagnosed as limb-girdle muscular dystrophy (LGMD) ( 9 , 10 ).…”
mentioning
confidence: 99%